Chemical investigation on Pseudoceratina purpurea collected from Banyuwangi Indonesia - Triana Hertiani; RuAngelie Edrada; Rob W.M. Van Soest; Werner E.G. Muller; Sudarsono .; Peter Proksch (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Chemical investigation on marine sponge Pseudoceratina purpurea collected from Banyuwangi, Indonesia has been performed. This study was aimed to isolate and to identify structures of the sponge secondary metabolites as well as to test their cytotoxicity activity on mouse lymphoma cell line L5178Y.Isolation procedure was performed by using different chromatography techniques. NMR spectroscopy and mass spectrometry methods were used to identify the compounds chemical structures. Cytotoxicity of the isolates was tested on mouse lymphoma cell line L5178Y by using the microculture tetrazolium (MTT) assay.This study yielded five known tyrosine-derived alkaloids, two of which, aplysamine-2 (1) and aeroplysinin-1 (2) showed growth inhibition of mouse lymphoma cell line L5178Y with IC50 value of 1.7 mg/mL and 0.57 mg/mL, respectively.Key words: Pseudoceratina purpurea, sponge, alkaloids.